INSTITUTION OF PRE-COURT AGREEMENT ON COOPERATION OF AN ACCUSED WITH A PROSECUTOR: ON THE OPTIMAL ESTABLISHED ORDER - A. A. Yunusov; N. N. Kovtun, (Russian Journal of Economics and Law)
The article analyzes the new criminal-procedural institution - pre-court agreement on cooperation of the accused and the prosecutor. The problems of theoretical and applied character are revealed, which occur at agreement conclusion. Basing on scientific positions of the well-known researchers, the author gives recommendations of law enforcement character.